Cover Image. (18th February 2022) - Fan, Cui; Wu, Jichang; Shen, Yilin; Hu, Haixia; Wang, Quan; Mao, Yufeng; Ye, Bin; Xiang, Mingliang
Abstract : The cover image is based on the Review Article Hypoxia promotes the tolerogenic phenotype of plasmacytoid dendritic cells in head and neck squamous cell carcinoma by Mingliang Xiang et al., https://doi.org/10.1002/cam4.4511 .